The Impact of Business Incubators on the Performance of the Entrepreneurial Ecosystem - Oana Pricopoaia; Stefan Adrian Susanu; Nicoleta Cristache; Irina Olimpia Susanu (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics)
More and more researchers are addressing in their work the importance of the interaction between entrepreneurship and sustainability in dynamic business environments. While research on the performance of entrepreneurial ecosystems has strengthened in recent years, a challenge remains to identify the role of incubators in this complex and elaborate context. In a qualitative approach, we explored the meanings, interpretations and subjective perspectives of the entrepreneurs participating in the research. For the exploratory analysis of the qualitative data, i.e. thematic content analysis, we used NVivo software. The aim was to identify clusters of words used by respondents, which, when analysed together, maximised the relevance of other words in the interviews, thus facilitating analyses of the business incubators in which these entrepreneurs operate. The study highlights various opportunities related to the role of business incubators, mainly generated by the increased awareness of entrepreneurs of the benefits they offer. Through this research, we aim to provide a clear understanding and insights that contribute to improving entrepreneurship and business incubation practices, supporting the development of entrepreneurs and ultimately resulting in economic growth and innovation.